TIME MANAGEMENT: PHILOSOPHICAL, PSYCHOLOGICAL, AND PRACTICAL ISSUES - Mamarajabova Iroda Fayzullayevna (Scholars Digest Publishing, 2025)
This article discusses the relativity of time, how it is perceived by individuals, its values, and the illusions surrounding progress. The focus is on the passage of time, its effective management, and how individuals assess time. The author examines the importance of time management using the mythological examples of Zeno and Sisyphus, and references Stephen Covey’s work, emphasizing the significance of time management. The article also explores scientific approaches to the relativity of time and the necessity of implementing time management in daily life.
Keywords: Time, relativity, planning, efficiency, progress, time management, Stephen Covey, Zeno, Sisyphus, motivation, philology, philosophy.